Analisis Kinerja Keuangan Berdasarkan Net Profit Margin (NPM), Return On Equity (ROE), Return On Asset (ROA), Gross Profit Margin (GPM) dan Harga Saham Pada PT. MEGA Perintis Tbk - Iwan Eka Putra; Aulia Yunicha Harly; Azizah Septia Ningrum; Faizal Riza (Universitas Muhammadiyah Jambi, 2024)
Financial performance is an important thing that needs to be known by internal and external parties. Because for internal parties it is used as a decision making tool to manage the company's finances well, while for external parties it is used as a decision making tool to carry out investment activities. For this reason, the author is interested in research with the title